Breast cancer‐specific survival by clinical subtype after 7 years follow‐up of young and elderly women in a nationwide cohort. Issue 6 (3rd December 2018) - Johansson, Anna L.V.; Trewin, Cassia B.; Hjerkind, Kirsti Vik; Ellingjord‐Dale, Merete; Johannesen, Tom Børge; Ursin, Giske
Abstract : Age and tumor subtype are prognostic factors for breast cancer survival, but it is unclear which matters the most. We used population‐based data to address this question. We identified 21, 384 women diagnosed with breast cancer at ages 20–89 between 2005 and 2015 in the Cancer Registry of Norway. Subtype was defined using estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor 2 (HER2) status as luminal A‐like (ER+PR+HER2‐), luminal B‐like HER2‐negative (ER+PR‐HER2‐), luminal B‐like HER2‐positive (ER+PR+/‐HER2+), HER2‐positive (ER‐PR‐HER2+) and triple‐negative (TNBC) (ER‐PR‐HER2‐). Cox regression estimated hazard ratios (HR) for breast cancer‐specific 7‐year survival by age and subtype, while adjusting for year, grade, TNM stage and treatment. Young women more often had HER2‐positive and TNBC tumors, while elderly women (70–89) more often had luminal A‐like tumors. Compared to age 50–59, young women had doubled breast cancer‐specific mortality rate (HR = 2.26, 95% CI 1.81–2.82), while elderly had two to five times higher mortality rate (70–79: HR = 2.25, 1.87–2.71; 80–89: HR = 5.19, 4.21–6.41). After adjustments, the association was non‐significant among young women but remained high among elderly. Young age was associated with increased breast cancer‐specific mortality among luminal A‐like subtype, while old age was associated with increased mortality in all subtypes. Age and subtype were strong independent prognostic factors. The elderly always did worse, also after adjustment for subtype. Tumor‐associated factors (subtype, grade and stage) largely explained the higher breast cancer‐specific mortality among young. Future studies should address why luminal A‐like subtype is associated with a higher mortality rate in young women. Abstract : What's new? Given the increasing numbers of patients with breast cancer, it is important to provide solid estimates of the breast cancer‐specific mortality across all age groups and clinical subtypes based on population‐based samples representative of the full spectrum of patients in the clinic. Using national cancer registry data, here the authors found that young women (<40) had a higher breast cancer‐specific mortality compared to screening‐aged women (50–69), in particular among luminal A‐like tumors, while older women (70–89) had a higher breast cancer‐specific mortality within all subtypes of breast cancer. Comorbidity is a potential explanation for the remaining survival deficit in elderly women.